Prevalence and Risk Factors of Adolescents Smoking: Difference Between Korean and Korean-Chinese - SoonBok E. Park, RN, PhD; Soon-Nyung Yoon, RN, PhD; Yunjeong Yi, RN, DrPH; Wenying Cui, RN, BSN; Bora Nam, RN, MSN (Elsevier, 2011)
Purpose: The purpose of this study was to compare smoking prevalence and risk factors of smoking between Korean and Korean-Chinese middle school students. Methods: Data was collected from seventh and eighth grade students from 12 schools in Korea and 6 schools in China. Descriptive statistics, Chi-square test, and t test were performed. Results: For data analysis 10,002 usable surveys were utilized. The smoking prevalence was higher in Korean-Chinese students than in Korean students. Risk factors, such as father smoking, friends smoking, gender, grade, academic achievement, alcohol use, and family income were associated with current smoking, and the differences in the two samples were significant. Korean-Chinese students were more likely than Korean students to have friends who smoked and a father who smoked. Smokers had a significantly higher rate of friends smoking, father smoking, and alcohol use. Korean-Chinese male students smoking prevalence was more than three times higher than Korean students. Korean students could sense a more anti-tobacco atmosphere in their environment. Korean-Chinese students were more likely than Korean students to perceive that it was easy to buy cigarettes and to smoke cigarettes in a public computer room. Conclusion: These results highlight the differences of smoking prevalence and risk factors between Korean-Chinese students and Korean students. The findings may help health educators and researchers to better understand adolescent smoking and risk factors cross culturally and aid in the development of more effective education programs, which could lead to preventing tobacco use among these populations.